Correlation between obesity, adipokines and the immune system - Marcos Regini Silveira; Anelena Bueno Frollini; Rozângela Verlengia; Cláudia Regina Cavaglieri (Universidade Federal de Santa Catarina, 2009)
Obesity is a worldwide health problem and the increase in its incidence, risks and consequences are a matter of growing concern. Obesity is characterized by the accumulation of fat in the body. Many studies are currently investigating obesity and associated comorbidities in an attempt to clarify the mechanisms involved. Fat tissue is a dynamic organ that secretes several factors, including adipokines. Adipokines are bioactive peptides secreted by fat cells, which are important for energy regulation and inflammatory and immune responses. Leptin, adiponectin and resistin are the most studied adipokines. The aim of this review was to gather information about these adipokines (leptin, adiponectin and resistin) and their relationship with the immune response in obese individuals, as well as the susceptibility of these patients to infections. The results of the literature review permit some observations. The circulating levels of these adipokines are directly involved in the degree of obesity of the patient. High or low circulating concentrations of these adipokines may have beneficial or negative effects on immune competence, with obese patients being more susceptible to infection and inflammation than eutrophic individuals.Key words: Obesity; Adipokines; Leptin; Adiponectin; Resistin; Immune system.